Comparison of hadron interaction models of EPOS LHC and QGSJETII-04 in the simulation of EAS using CORSIKA-77410 - Yerezhep, Н.О.; Saduyev, Н.О.; Kalikulov, О.А.; Banshchikova, М.А. (Recent Contributions to Physics, 2024)
The article presents a comparative analysis of two high-energy hadronic interaction models, EPOS LHC v3400 and QGSJET-II-04, combined with the low-energy interaction model GHEISHA 2002d (double precision), for primary particles such as protons and iron in the energy range of 1016-1019 eV using the CORSIKA-7.7410 program. Key air shower parameters, including the depth of maximum Xmax, muon distributions, energy distribution of secondary particles, and horizontal distribution, were analyzed. The results reveal the strengths and limitations of each model, providing recommendations for their application in cosmic ray research. The results provide a deeper understanding of the characteristics of secondary cosmic rays at the observation level of the Tien Shan High-Altitude Scientific Station (3340 m above sea level) and are intended to support future experiments focused on EAS core studies by the «Burst Detector». The features of each model were determined, and their influence on key EAS parameters, as well as their applicability in improving the interpretation of experimental data, were assessed. The study outlines the fundamental principles and characteristics, as well as the theoretical knowledge required to understand the simulated effects. The scope of application is defined, and the data calibration process and computational complexity of the EPOS and QGSJET models are described. A comparison of the total number of particles for protons, oxygen, and iron between the EPOS and QGSJET-II models is provided.